The Influence of the Independence of the Board of Directors, Audit Committee, and Background of the Board of Directors on Fraud Detection - Fransiskus Selamat Putra Zebua; Melisa Anggraini; Dwi Hayu Estrini (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2026)
This study aims to analyze the influence of the elements of corporate governance on fraud detection. Fraud in financial statements is an important issue because it can reduce the credibility of the company, reduce investor confidence, and weaken the effectiveness of corporate governance. This research uses a quantitative approach with secondary data obtained from the company's annual reports and financial statements. The sampling technique used was purposive sampling, and 134 observation data were obtained. Data analysis was carried out using multiple linear regression by first performing classical assumption tests, which included normality, multicollinearity, autocorrelation, and heteroscedasticity tests. Fraud detection was measured using the F-Score method, while the independence of the board of directors was measured by the proportion of independent directors, the audit committee was measured by the frequency of meetings, and the background of the board of directors was measured by the proportion of directors who had economic or financial education. The results of the study show that the elements of corporate governance have a significant effect on fraud detection with negative coefficients. These findings indicate that the improvement of the governance mechanism is likely to be followed by a decrease in the rate of fraud detection, which reflects that the monitoring mechanism functions more as a preventive measure than the detection of fraud. This research provides the implication that the effectiveness of corporate governance does not only depend on formal structures, but also on the quality of implementation, competence, and substantive independence in carrying out supervisory functions.